Posted by **Paul C** on Sunday, November 26, 2006 at 6:08pm.

Show that 1-cos2A/Cos^2*A = tan^2*A

1-cos2A/Cos^2*A =

[Cos^2(A) - Cos(2A)]/Cos^2(A).

Substitute:

Cos(2A) = 2Cos^2(A) - 1:

[1 - Cos^2(A)]/Cos^2(A)=

Sin^2(A)/Cos^2(A) = tan^2(A)

## Answer this Question

## Related Questions

- Trig - Given: cos u = 3/5; 0 < u < pi/2 cos v = 5/13; 3pi/2 < v < ...
- Mathematics - Trigonometric Identities - Let y represent theta Prove: 1 + 1/tan^...
- calculus - Differentiate. y= (cos x)^x u= cos x du= -sin x dx ln y = ln(cos x)^x...
- Calc. - Differentiate. y= (cos x)^x u= cos x du= -sin x dx ln y = ln(cos x)^x ln...
- Math - Solving Trig Equations - What am I doing wrong? Equation: sin2x = 2cos2x ...
- TRIG! - Posted by hayden on Monday, February 23, 2009 at 4:05pm. sin^6 x + cos^6...
- precalculus - For each of the following determine whether or not it is an ...
- trig - Reduce the following to the sine or cosine of one angle: (i) sin145*cos75...
- Math - Prove each identity: a) 1-cos^2x=tan^2xcos^2x b) cos^2x + 2sin^2x-1 = sin...
- pre-cal - Simplify the given expression........? (2sin2x)(cos6x) sin 2x and cos ...